Poseidon's arrow [large type] - Cussler, Clive (Cussler, Clive. Dirk Pitt adventure., 2012)
Ruthless Austrian entrepreneur Edward Bolcke has managed to steal a crucial component of the U.S. Navy's latest submarine technology--and he has found a way to hijack the world's supply of rare earth minerals. The three Pitts, along with longstanding sidekick Al Giordino, use their usual mix of brains and brawn to see that justice is served